The antioxidant role of pumpkin (Cucurbita pepo) seed extract against acute reproductive toxicity by uranyl acetate in male rats - Ghusoon Abdul Kareem Neamah; Muna Abdul Sahib Alkhfaji; Heba Saleh Shaheed (Journal of Advanced Veterinary and Animal Research, 2023)
Objective: The main goal of the study was to find whether pumpkin (Cucurbita pepo) extract has any preventive or antioxidant properties against acute uranyl acetate (UA)-induced reproductive cytotoxicity. Material and Methods: Four groups each, including 10 adult male rats, were randomly assigned. (GI): the control group was given 1 ml of purified water orally for 30 days. (GII): Rats were given orally, a single dose of 150 mg/kg b.w. UA (GIII): Rats consumed 40 mg/kg b.w. of pumpkin seed extract (PSE) orally every day for 30 days. (GIV): Rats received a single dose (150 mg/kg b.w.) of UA plus a daily oral dose of PSE (40 mg/kg b.w.) for 30 days. Animal sacrifice was used for oxidative stress and histopathological study. Results: Showed significantly (p ≥ 0.001) elevated malondialdehyde levels in the GII group (6.19 ± 0.4), while GIII and GIV showed no significant differences. Glutathione peroxidase showed a significant (p ≥ 0.001) decrease (2.55 ± 0.2) in the GII group, while in groups (GIII and GIV), it showed a significant (p ≥ 0.001) increase (4.61 ± 0.16, 4.28 ± 0.032), respectively. The histopathological study for GII groups showed sloughing of epithelial cells lining the seminiferous tubules with a decrease in the number of spermatozoa in some tubules. Many sections revealed hyperplasia of the epithelial cells lining the seminiferous tubules with necrosis. The GIII and GIV groups showed normal histological structures with an increase in spermatogenesis in the testes and epididymis tissues. Conclusion: We concluded that UA causes oxidative stress and histopathological alterations in the rat reproductive system. Pumpkin extract plays a role in improving the activity of the reproductive system. [J Adv Vet Anim Res 2023; 10(4.000): 647-653]